Towards a cooperative traffic network editor - José L. F. Pereira (2009)
In this paper we explore the potential benefits of concepts such as visual interactive modelling and simulation to devise and implement a cooperative network editor embedded in a collaborative environment for transport analysis. Traditional approaches lack adequate means to foster integrated analyses of transport systems either because they are strict in terms of purpose or because they do not allow multiple users to dynamically interact on the same description of a model. The use of a common geographical data model of the application domain promotes the means for different experts to interact seamlessly in a collaborative environment.